ROLE OF AMBROXOL AS A PROPHYLACTIC AGENT AGAINST COVID-19 - Baraka, Azza M.; El-Hadidy, Wessam F. (Universal Journal of Pharmaceutical Research, 2021)
Currently the world is facing a pandemic disease, namely Coronavirus disease 2019 (COVID-19) that is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). As finding recent drugs targeting COVID-19 will take a long time, so repositioning currently existing FDA approved drugs for treating this disastrous disease is an acceptable solution. It has been found that for SARS-CoV-2 to be infective, this necessitates splitting of the viral spike glycoproteins by the serine protease “type II transmembrane serine protease TMPRSS2” that has shown to be widely expressed in pulmonary tissues. Thus, TMPRSS2 is suggested to be potential target for antiviral drug design against COVID-19. The mucokinetic drug “Ambroxol” has been reported as a potent inhibitor of TMPRSS2, thus it could represent a therapeutic as well as a prophylactic candidate against SARS-CoV2. This review gives a brief summary about ambroxol’s potential role against COVID-19’s TMPRSS2. Peer Review History: Received 2 December 2020; Revised 6 January 2021; Accepted 10 February; Available online 15 March 2021 Academic Editor: Dr. DANIYAN Oluwatoyin Michael , Obafemi Awolowo University, ILE-IFE, Nigeria, toyinpharm@gmail.com Reviewer(s) detail: Dr. Nuray Arı , Ankara University, Turkiye, ari@ankara.edu.tr Prof. Cyprian Ogbonna ONYEJI , Obafemi Awolowo University, Ile-Ife, Nigeria, conyeji@oauife.edu.ng Dr. Asia Selman Abdullah , Al-Razi university, Department of Pharmacy, Yemen, asia_abdullah65@yahoo.com